Islam dan Budaya Jawa, Pertemuan yang Terus Berkelanjutan - Priyatna, Yana; Sukmaranti, Galuh (FISIP Universitas Bung Karno, 2025)
The synthesis between Islam and Javanese culture is presented in a book by Mark R. Woodward, who conducts ethnographic research and studies the manuscripts written by court scholars in Java. Javanese Islam, as analyzed in Woodward’s book